Representation through translation : all things spicy give you a case of the "Delhi-belly". - Sukumar Sri Durga. (2009)
The translation and subsequent adaptation of a novel into the film medium mirrors the act of being ‘borne across’, thereby emulating the diasporic experience and the processes of cultural syncretism. The translation from novel to film calls for the meaning of a literary text to be borne across to a different medium albeit one that operates primarily via a visual discourse. The act of translation from the literary medium to the film medium cannot take place without the act of negotiation. This follows Christine Gledhill’s argument in “Pleasurable Negotiations” that in any textual subject “meaning is neither imposed nor passively imbibed, but arises out of a struggle or negotiation between competing frames of reference, motivation and experience” (Gledhill 114). In this case, it refers to the act of adaptation that deliberately selects and rejects modes of representation in order to access and assimilate the dominant discourse or culture successfully. What manifests from filmmakers’ efforts to appeal to popular culture is the utilization of exotica and pastiche as tools of negotiation into dominant discourse which ironically led to an unconscious subjugation of the minority culture to the voyeuristic gaze of the global audience and the typifying the minority culture based on a monolithic experience.